Progressive peer evaluation: Important but absent in EFL speaking classes - Bustami Usman; Asnawi Muslim; Ibrahim C.R. Champion; Iskandar Abdul Samad (Studies in English Language and Education, 2018)
Comprehensive teaching-learning about speaking evaluation, especially peer evaluation, is conspicuous by its absence in English Foreign Language (EFL) Speaking classes at all secondary and tertiary levels in Indonesia, especially in Aceh, This comparative research study looks at the various aspects used for evaluation and especially looks at peer evaluation in EFL speaking classes in Aceh. The paper describes twenty three (23) components recommended for evaluation of speaking communications: the seen, the spoken and the script (content) components. The results showed that teachers of EFL speaking are not using and are not even taught such detailed evaluation systems. Moreover the syllabi for speaking English at upper secondary level are severely lacking as are those used in tertiary courses. Educators need to learn from the Toastmasters International systems for evaluation and for making evaluation speeches, in particular the need to prioritise praise in evaluation with only a pointer or two on how to improve the next speech. This paper includes a simplified format for peer evaluations that students can easily be taught to use and also stresses the need for praise, not punishment, for successful evaluation. Teachers of Speaking English EFL, who practice the recommendations from this paper, should get much better results from their students.